Perancangan Desain UI/UX Aplikasi Manajemen Keuangan Menggunakan Metode Design Thinking - Tangka, George William Morris; Lompoliu, Erienika Meiling (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Money is widely accepted and trusted by society as a medium of payment or transaction, facilitating the exchange of goods and services. In everyday life, individuals face daily expenses that need effective management. The lack of awareness and knowledge about the importance of financial planning and management among students and young adults leads to significant financial problems. This study aims to design a financial management application with a focus on user-friendly and enjoyable UI/UX design. The application will help users manage their income, expenses, and savings efficiently. Key features include daily transaction records, bill payment reminders, expense analysis, and financial tips to achieve financial goals. The goal is to enable users to handle their finances more wisely. By applying the Design Thinking method, the research addresses complex financial management issues innovatively and comprehensively. Results from usability testing indicate that screens like the Select Category achieved a perfect usability score of 100, while others like the Expense Pages showed recurring issues with high misclick rates, highlighting areas for improvement. Overall, the average usability score was 75, suggesting room for enhancement.